(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2024)
The article aims to provide a critical examination of the concept of environmental crime, analyzing the relationship between the mafia phenomenon and the environment through a multidisciplinary approach and the theoretical tools of green criminology and organized crime studies. Treating the Italian case in particular, the legal implications of the phenomenon will then be analyzed, with reference to the instruments of criminal law. Finally, the case of waste trafficking will be considered.